Research on the Performance of Integrated Gate Commutated Thyristor - 吴煜东; 陈芳林; 雷云; 蒋谊 (Kongzhi Yu Xinxi Jishu)
It presented the structure of IGCT and its features in four operating stages (blocking state, turn-on, on-state and turn-off). It introduced the main parameters and application notices in the four operating stages.